Experiencias TIC en la Educación Inicial en Colombia durante la Pandemia: Análisis de Desafíos y Oportunidades. (2023)
The global outbreak generated by the pandemic (COVID-19) has disrupted countless aspects of society.In Colombia, the education sector was seriously affected. Educational institutions had to quickly adapt todistance education, using Information and Communication Technologies (ICT) as a key tool, especially ininitial education. This article examines teachers' experiences of incorporating ICT into this level of educationduring the pandemic. The transition from an in-person to a virtual educational environment has raisedimportant questions in terms of equity, privacy, educational quality, and student well-being. At the same time,it has opened the door to new forms of teaching and learning that deserve to be explored and made the mostof.